2011
DOI: 10.1007/bf03356380
|View full text |Cite
|
Sign up to set email alerts
|

Microbial enrichment of compost with biological control agents to enhance suppressiveness to four soil-borne diseases in greenhouse

Abstract: The aim of the present work was to study if the level and reproducibility of suppressive properties of compost can be increased upon enrichment with biological control agents. A compost made from green waste, organic urban waste and urban sludge was inoculated with commercial formulations of Trichoderma and non-pathogenic Fusarium. The compost showed to be suppressive against some soil-borne pathogens, except R. solani, while such activity was lost after sterilisation. The suppressive effect of enriched compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
38
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(44 citation statements)
references
References 15 publications
6
38
0
Order By: Relevance
“…Hence, this BCA would be the most preferred component in an amendment of a biological control compost or biofertilizer. According to Pugliese et al (2011) and Harman et al (2004), Trichoderma as a component in compost could lead to a substrate with broader-range suppressive effects. However, this present study demonstrated that consortium of T. harzianum and B. cereus was less effective in controlling Ganoderma disease of oil palm at nursery trial compared to individual application of the BCAs.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, this BCA would be the most preferred component in an amendment of a biological control compost or biofertilizer. According to Pugliese et al (2011) and Harman et al (2004), Trichoderma as a component in compost could lead to a substrate with broader-range suppressive effects. However, this present study demonstrated that consortium of T. harzianum and B. cereus was less effective in controlling Ganoderma disease of oil palm at nursery trial compared to individual application of the BCAs.…”
Section: Discussionmentioning
confidence: 99%
“…This combination of beneficial microbes also had the added effect of stimulating plant N and P absorption (Hernandez and Chailloux 2004). Formulations of compost with beneficial bacteria have also shown the ability to suppress plant pathogens (Pugliese et al 2011;Yang et al 2011). The ability of formulations of multiple beneficial microbes to increase plant productivity and health hint at the potential of the entire microbiome and plants working together with mutually beneficial outcomes.…”
Section: Role Of Soil Microbes In Soil Health and Plant Productivitymentioning
confidence: 99%
“…Enrichments in composting improve nutritive value; augment disease suppressive activity and beneficial microbial populations in the composts (Postma et al 2003;Biswas and Narayanasamy 2006;Pugliese et al 2011;Diaz et al 2011;Singh and Amberger, 1995;Nishanth and Biswas 2008;Biswas 2011;Meena and Biswas 2014). Such enriched composts partly substitute mineral fertilizer requirements (Adamtey et al 2009), improve soil organic matter stocks, augument soil quality and most importantly prevent loss of nutrient N through volatilization (DeLaune et al 2004;Steiner et al 2010).…”
Section: Introductionmentioning
confidence: 99%